2021
DOI: 10.1016/j.crfs.2021.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Impact of food texture modifications on oral processing behaviour, bolus properties and postprandial glucose responses

Abstract: Several studies have demonstrated food texture manipulation on oral processing behaviour (OPB). We explored the effect of texture-differences of equivalent carbohydrate load on OPB, bolus properties and postprandial glycaemic responses (PPG). In a randomised cross-over, within-subjects, non-blinded design, healthy male participants (N = 39) consumed fixed portions of white rice (WR) and rice cake (RC) while being video recorded to measure microstructural eating behaviours. PPG was compared between test foods o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 59 publications
(86 reference statements)
0
10
0
Order By: Relevance
“…Recent findings demonstrate that food texture modifications for an equivalent carbohydrate load stimulate differences in oral processing, which result in differences in bolus surface area and saliva uptake which were associated with changes in temporal glucose release. 48 Differences observed between faster and slower eaters can also be reflected in bolus properties at swallow, and the resultant glucose and insulin responses, suggesting that texture modifications will interact with eating style in how they influence metabolic responses. 36,49 Further research is needed extend the findings of the current study to differences in food bolus properties across different textures to better understand the impact on metabolic responses.…”
Section: Papermentioning
confidence: 99%
“…Recent findings demonstrate that food texture modifications for an equivalent carbohydrate load stimulate differences in oral processing, which result in differences in bolus surface area and saliva uptake which were associated with changes in temporal glucose release. 48 Differences observed between faster and slower eaters can also be reflected in bolus properties at swallow, and the resultant glucose and insulin responses, suggesting that texture modifications will interact with eating style in how they influence metabolic responses. 36,49 Further research is needed extend the findings of the current study to differences in food bolus properties across different textures to better understand the impact on metabolic responses.…”
Section: Papermentioning
confidence: 99%
“…The texture difference might not be as great as to induce significant physiological effect when co-ingested with rice. It is suggested that the texture variation of non-carbohydrate foods may not make a significant difference on postprandial GR and IR as the texture variation of carbohydrate foods did [ 52 , 53 , 54 ]. Furthermore, the effect of the mastication might be overshadowed by individual variation in the capacity of oral processing and the favorite hardness of cooked broccoli.…”
Section: Discussionmentioning
confidence: 99%
“…Food can influence eating rate but also oral processing and saliva-bolus uptake during the oral phase of digestion. Differences in food oral processing behavior have been shown to contribute to temporal changes in post-prandial glucose and insulin, and post-meal satiety responses (65)(66)(67). Slower eating rates result in greater bolus surface area, saliva uptakes and may have an incretin effect as early glucose release stimulates greater early insulin release (36,65).…”
Section: Food Texture Eating Rate Energy Intake and Metabolismmentioning
confidence: 99%